Samardha InfoTech : a specially-abled organization - Vashisth, Tarun, (SAGE business cases., 2020)
Samardha InfoTech is an organization based in Ahmedabad that deals in low-end BPO tele-services. It believes in providing employment to the needy, and 60% of the employees are persons with various types of disabilities. Samardha strives to create an all-inclusive environment so that the employees with disabilities, along with non-disabled employees, could perform to their potential. Current operations encompass a tele-verification process for a telecom company and a credit card sales process for a bank. Samardha plans to go international in the near future, with processes for an Australian telecommunication company and a South African ERP solutions provider company. Besides providing a business case for employing and managing employees with disabilities in particular, and a diverse workforce in general, the case raises questions as to whether Samardha will be able to emulate its values and culture in these new processes, and whether Samardha will be able to reconcile low-skill employees with employees having complex skill-sets hired for the new processes.